THE MINDSET OF PHYSICAL EXERCISE (PE) TEACHERS IN DISTRICT 134 UNPAS ON THEIR UNDERSTANDING OF PHYSICAL EDUCATION AFTER COMPLETING IN-SERVICE TEACHER EDUCATION AND PROFESSIONAL TRAINING (PLPG) - Sobarna, Akhmad (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2015)
This study is intended to describe the mindset of Physical Exercise (henceforth PE) teachers on physical education after completing in-service teacher education and professional training (henceforth PLPG). This study employed qualitative descriptive method. The population of this study is PE teachers in district 134 UNPAS that includes Karawang area, the city/the regency of Bogor, West Bandung regency, Â the city/the regency of Sukabumi, Cianjur, Purwakarta, Subang, Cimahi, and Bekasi. The sample of this study was 29 participants. The sample was drawn by means of incidental sampling method. The data collection instrumen used is rating scale mindset of the participantsâ understanding of physical education. The data was further analyzed by using descriptive analysis technique. The findings show that the level of understanding of the PE teachers about the implementation of reached 89% which belong in the criterion âvery goodâ. The description of every indicator demonstrates that: a) the perception of physical exercise teaching as much as 88,5% is categorized as good, b) physical education knowledge is considered as good as much as 89,5%, c) the effort to enhance teaching skills is 79,3%, which belongs in the criterion âgoodâ. In conclusion, generally, the mindset of the participants in district 134 UNPAS in understanding the aspect of physical education implementation reached 89% with the criterion âvery goodâ. This implication of this study is that in the implementation of PLPG, the emphasis should be paced upon enhancing understanding of physical education concept and the effort to hone the ability in teaching physical exercise in creative and innovative fashion.